Paget–Schroetter syndrome without anatomical abnormalities of the thoracic outlet – A case report - Balaji Zacharia; Anoop Antony (Journal of Orthopaedic Reports)
Background: One uncommon cause of unilateral upper limb swelling is Paget-Schrotter syndrome(PSS). We present case of PSS in middle-aged man. Case report: A 45-yrs old manual laborer came to us with right upper limb pain and swelling for two days. He is a right-hand dominant person. He repeatedly lifted heavy weights on the previous day. His right arm and shoulder were swollen. There was dilatation of the right cephalic vein. His routine blood examination and radiographs of the right shoulder and chest were normal. A venous Doppler scan revealed acute thrombosis involving the entire length of the right subclavian vein. A CT venogram confirmed this finding. He was treated with anticoagulants. He achieved complete symptom relief after six months of treatment. Conclusion: The diagnosis of PSS demands a considerable degree of suspicion. Complications might be avoided by early diagnosis and prompt treatment.